The effectiveness of environment assessment tools to guide refurbishment of Australian residential aged care facilities: A systematic review - Neylon, S.; Bulsara, C.; Hill, Anne-Marie (Wiley-Blackwell Publishing Asia, 2016)
Objective: To determine applicability of environment assessment tools in guiding minor refurbishments of Australian residential aged care facilities. Method: Studies conducted in residential aged care settings using assessment tools which address the physical environment were eligible for inclusion in a systematic review. Given these studies are limited, tools which have not yet been utilised in research settings were also included. Tools were analysed using a critical appraisal screen. Results: Forty-three publications met the inclusion criteria. Ten environment assessment tools were identified, of which four addressed all seven minor refurbishment domains of lighting, colour and contrast, sound, flooring, furniture, signage and way finding. Only one had undergone reliability and validity testing. Conclusion: There are four tools which may be suitable to use for minor refurbishment of Australian residential aged care facilities. Data on their reliability, validity and quality are limited.